2023
DOI: 10.1111/gcb.16671
|View full text |Cite
|
Sign up to set email alerts
|

Toxic temperatures: Bee behaviours exhibit divergent pesticide toxicity relationships with warming

Abstract: Climate change and agricultural intensification are exposing insect pollinators to temperature extremes and increasing pesticide usage. Yet, we lack good quantification of how temperature modulates the sublethal effects of pesticides on behaviours vital for fitness and pollination performance. Consequently, we are uncertain if warming de-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 153 publications
1
12
0
Order By: Relevance
“…Neonicotinoids reduce the ability of honeybees to survive exceptionally warm or cold temperatures [12,13]. A recent study also found that the neonicotinoid imidacloprid interacted with high temperatures to reduce the distances that bumblebees were able to fly in a tethered flight mill [16]. Our study focused on homing success, but also required bees to fly one kilometre, a distance which may have been challenging for Pristine-exposed bees, particularly at higher temperatures.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Neonicotinoids reduce the ability of honeybees to survive exceptionally warm or cold temperatures [12,13]. A recent study also found that the neonicotinoid imidacloprid interacted with high temperatures to reduce the distances that bumblebees were able to fly in a tethered flight mill [16]. Our study focused on homing success, but also required bees to fly one kilometre, a distance which may have been challenging for Pristine-exposed bees, particularly at higher temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…Neonicotinoids reduce the ability of honeybees to survive exceptionally warm or cold temperatures [12,13], with greater differences in gene expression found in bees exposed to both stressors as opposed to one or the other [12,14,15]. A recent study also found that the neonicotinoid imidacloprid interacted with high temperatures to reduce the distances that bumblebees were able to fly in a tethered flight mill [16].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the interaction between temperature and neonicotinoids may depend on the type of behavior being observed. Neonicotinoids had a greater effect on movement and food consumption at a low temperature (21°C) yet a greater effect on flight distance at a high temperature (30°C) (Kenna et al 2023). Considering 13/129 studies reported temperature from our analysis of ECOTOX, monitoring temperature can be critical to interpreting data used for risk assessments.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that environmental conditions usually differ dramatically from lab conditions, that environmental conditions such as temperature affect toxicity (Kenna et al. 2023 ), and that for eusocial insects, colony-level testing is critical to assess effects on reproduction, mandating higher-tier field-realistic testing before approval decisions are made could significantly lower threats to pollinator safety (figure 1 ). In addition, pesticides should be tested as they are formulated and sold for real-world use to account for the potential effects of inert ingredients and the synergisms between formulation components.…”
Section: Solutionsmentioning
confidence: 99%